A Foresight Study of European East-West Agrifood Trade Options - George Philippidis; Ana Sanjuań; Andrzej Tabeau; Siemen van Berkum; Monika Verma (German Journal of Agricultural Economics (GJAE), 2018)
Taking a trade perspective with a focus on agrifood markets, the current foresight study employs a computable general equilibrium simulation model to quantify the implications of different future pathways of European East-West trade relations for the Commonwealth of Independent States (CIS), thereby providing insight on how best to orientate their political and trade strategies. Comparing with a baseline, two optimistic pathways explore greater market access, both within Europe ('Deep integration') and globally ('trade liberalisation'). In contrast, an isolationist 'trade bloc' pathway reflecting a deteriorating political situation between Russia and the West is also examined. In the 'baseline', Deep and Comprehensive Free Trade Agreement (DCFTA) members realise market gains, whilst intra-CIS trade diversion effects are small. The 'deep integration' scenario ('liberalisation' scenario) generates significant relative benefits for DCFTA signatories' agrifood (non-agrifood) activities. In both of these trade reform narratives, the Eurasia Economic Union (EAEU) economic gains are biased in favour of Russia's energy sector resulting in greater import dependence on agrifood commodities from the EU. The isolationist trade narrative nurtures EAEU agrifood activity, although at the cost of its macroeconomic growth.
Keywords: 330